Communication Media Design for Children with Autism Spectrum Disorder - Nurhadi; Supardi U.S; Hasbullah (Jurnal Penelitian dan Pengembangan Pendidikan, 2026)
Communication is a crucial aspect in expressing desires and building social interactions. Children with Autism Spectrum Disorder (ASD) often experience barriers in verbal and nonverbal communication, which impact daily behavior and the learning process. This study aims to identify the need for communication media appropriate to the characteristics of children with ASD as a basis for developing effective learning media. This study used a qualitative descriptive approach with a case study design. The subjects in this study were 4 teachers who teach children with Autism Spectrum Disorder (ASD) and 4 children with ASD as students at the Autism Special School. Data were collected through structured interviews and observations of four teachers and four children with ASD at the special school—data analysis used thematic analysis. The study found that concrete objects and picture cards were used to help children gradually understand the concepts. This study concluded that communication learning for children with ASD requires a structured, individualized approach, supported by media appropriate to the child's characteristics. The implications of this study emphasize the importance of developing visual and technology-based learning media, increasing collaboration between teachers and parents, and providing teachers with training in managing children's behavior and in utilizing adaptive learning media to make the learning process more effective.